Ten years of CR physics with PAMELA. Issue 10 (15th November 2018) - Galper, A.; Spillantini, P.
Abstract: The satellite borne Pamela instrument is dedicated to the precise and high statistics study of cosmic-ray fluxes over a four decades energy range. Pamela experiment is the last step of the 'Russian-Italian Mission' (RIM) program established in 1992 between several Italian and Russian institutes and with the participation of Sweden and Germany. Designed as a cosmic ray observatory at 1 AU, its extensive program is made possible thanks to the outstanding performance of the instrument, the low energy threshold, the quasi-polar orbit and the 10 years duration of the observation. The physics program pays particular attention to the study of particles and antiparticles fluxes and includes search for dark matter, primordial antimatter, new matter in the Universe, study of cosmic-ray propagation, solar physics and solar modulation, and terrestrial magnetosphere. Very important is the discovery of the anomalous increase of the positron flux at energies higher that 10 GeV (the so called 'Pamela anomaly'), and the abrupt spectral hardening of H and He, challenging the current paradigm of cosmic-ray acceleration and propagation in the Galaxy.